(untitled) (Research, Society and Development, 2020)
This study aimed to report the experience of a project of integrative and complementary practices carried out by health professionals in a public hospital in the city of Rio de Janeiro. This is an exploratory and descriptive experience report of students participating in an extension project on the applicability of integrative practices for stress reduction in SUS health professionals, carried out in 2019 in a public hospital in the city of Rio of January. According to the professionals who participated, the activities developed were effective in relieving the stress and tension and stress caused by work in the professionals who participated. For the students who performed the integrative practices, the experience was rewarding both professionally and personally, because in addition to stimulating the practice of a subject little addressed in the context of undergraduate nursing, it also allowed to understand the need for rest that health professionals have and the possibility of promoting this with simple and accessible practices. Integrative practices are shown as measures to help relieve the stress of health professionals. It is important that new research and studies are carried out in order to seek to understand more the effects of practices on health professionals.